Effect of solution temperature on microstructure and mechanical properties of selective laser melted Fe–22Cr–5Ni-0.26N duplex stainless steel - Hongliang Xiang; Wei Zhao; Yanjin Lu (Journal of Materials Research and Technology, 2022)
Selective Laser Melting (SLM) technology is effective for fabricating complex shape parts with superior strength and ductility. However, the high-temperature gradient and rapid solidification rate in the SLM process led to unstable material microstructure, which indicated an excellent strength and poor elongation of the SLM specimen. In order to achieve outstanding strength-plasticity matching, the influences of different solution temperatures (1000 °C, 1100 °C, and 1200 °C) on the evolution of phase and microstructure of Fe–22Cr–5Ni-0.26 N duplex stainless steel (DSS) fabricated by SLM were investigated. The results were then used to clarify the corresponding variations in mechanical properties of the specimens under tensile loading. The results revealed that the AS-SLM specimen showed high yield strength and poor elongation which was 1162.52 MPa and 4.97%. Solution treatment at 1000 °C can increase the elongation from 4.97% to 29.21% due to the two-phase structures recovered, grains refined, as well as eliminate dislocation and residual stress through recrystallization. As the temperature rose, the yield strength declined, while elongation remained almost unchanged. Except for elongation, the tensile strength, yield strength, and hardness were all higher than those of forged specimens. Therefore, solution treatment is an efficient strategy to improve the mechanical properties of the SLMFe-22Cr–5Ni-0.26 N DSS with excellent yield strength and plasticity.